2020
DOI: 10.1103/physrevd.102.036019
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive spectra and Bose-Einstein correlations in small thermal quantum systems

Abstract: The spectra and correlation of identical particles emitted from small local-equilibrium sources are considered. The size of the system is defined by the negative part of the parabolic falling chemical potential. The analytical solution of the problem is found for the case of inclusive measurements. It is shown that in the case where the size of the system is comparable to the thermal wavelength of the particles, the spectra and correlation functions are far from the quasiclassical approximation expected for la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Now, let us apply the fixed particle number constraint to the grand-canonical statistical operator (8) to define canonical statistical operator ρ N . For this aim, one can utilize the projection operator P N ,…”
Section: Ideal Gas Of Bosons In a Harmonic Trap With Fixed Particle N...mentioning
confidence: 99%
See 1 more Smart Citation
“…Now, let us apply the fixed particle number constraint to the grand-canonical statistical operator (8) to define canonical statistical operator ρ N . For this aim, one can utilize the projection operator P N ,…”
Section: Ideal Gas Of Bosons In a Harmonic Trap With Fixed Particle N...mentioning
confidence: 99%
“…The detail analysis of inclusive spectra and Bose-Einstein correlations in small thermal quantum systems was done very recently in Ref. [8]. It is shown that non-trivial coherence parameter appears in inclusive two-boson spectra only in the case of coherent condensate formation.…”
Section: Introductionmentioning
confidence: 99%